The Influence of Transformational Leadership, Interpersonal Trust, P-O Fit on Innovative Work Behavior and Knowledge-sharing Behavior as mediation - Rochani, Supargono; Suwarto, F. X (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Public organizations must continue to develop efficient and adaptive public services as their competitive advantage. One important strategy in this effort is to increase employee innovative work behavior. The purpose of this research is to explore the factors that influence Innovative Work Behavior of government employees, including Transformational Leadership, P-O Fit, and Interpersonal Trust with Knowledge-sharing Behavior as mediation. The research uses a quantitative approach using the SEM model and smartPLS application to analyze data from 292 functional employees at the Directorate General of Customs and Excise. The results of the analysis show that Transformational Leadership and P-O Fit are positively related to IWB. Meanwhile, Interpersonal Trust does not have a direct influence on IWB but has a positive impact through Knowledge-sharing Behavior as a mediator. One application of this managerial research is to increase Knowledge-sharing Behavior. This can be achieved through development strategies that involve active employee participation, expanding their access to knowledge that can trigger creativity and innovation, and building information systems with open access to all employees. Suggestions for further research are to consider organizational factors that are responsive to change (agile organization) in model analysis so that it can provide a more comprehensive understanding of the factors that influence Innovative Work Behavior in the context of the dynamics of organizational change.